Allosteric interactions between receptor site 3 and 4 of voltage-gated sodium channels: a novel perspective for the underlying mechanism of scorpion sting-induced pain. Issue 1 (December 2015) - Feng, Yi-Jun; Feng, Qi; Tao, Jie; Zhao, Rong; Ji, Yong-Hua
Abstract Background BmK I, a site-3-specific modulator of voltage-gated sodium channels (VGSCs), causes pain and hyperalgesia in rats, while BmK IT2, a site-4-specific modulator of VGSCs, suppresses pain-related responses. A stronger pain-related effect has been previously attributed toButhus martensi Karsch (BmK) venom, which points out the joint pharmacological effect in the crude venom. Methods In order to detect the joint effect of BmK I and BmK IT2 on ND7-23 cells, the membrane current was measured by whole cell recording. BmK I and BmK IT2 were applied successively and jointly, and the synergistic modulations of VGSCs on ND7-23 cells were detected. Results Larger peak INa and more negative half-activation voltage were elicited by joint application of BmK I and BmK IT2 than by application of BmK I or BmK IT2 alone. Compared to the control, co-applied BmK I and BmK IT2 also significantly prolonged the time constant of inactivation. Conclusions Our results indicated that site-4 toxin (BmK IT2) could enhance the pharmacological effect induced by site-3 toxin (BmK I), suggesting a stronger effect elicited by both toxins that alone usually exhibit opposite pharmacological effects, which is related to the allosteric interaction between receptor site 3 and site 4. Meanwhile, these results may bring a novel perspective for exploring the underlying mechanisms of scorpion sting-induced pain.